Cost-effectiveness analysis of penpulimab combined with paclitaxel and carboplatin as first-line treatment for advanced squamous non-small cell lung cancer - You, Xiaoyan; Qin, Jiali; Wang, Xiaomei; Wang, Xianying (Frontiers in Pharmacology, 2025)
BackgroundAdvanced or metastatic squamous non-small cell lung cancer (NSCLC) represents a significant clinical and economic burden globally. In China, the introduction of innovative immunotherapy agents, such as penpulimab, has the potential to improve patient outcomes, but their high cost raises questions about affordability and cost-effectiveness.ObjectiveThis study evaluates the economic viability of penpulimab combined with paclitaxel and carboplatin as a first-line treatment for this patient population.MethodsData were obtained from the published randomized controlled trial AK105-302. A three-state partitioned survival model was developed to estimate the cost-effectiveness of the two treatments. One-way deterministic sensitivity analysis, probabilistic sensitivity analysis, and scenario analyses were performed to assess the robustness of the results and explore variations in key parameters.ResultsThe incremental cost-effectiveness ratio (ICER) for the penpulimab group compared to the placebo group was $16,105.90 per quality-adjusted life year (QALY), which falls below the willingness-to-pay (WTP) threshold of $37,709.46 per QALY. Deterministic sensitivity analysis identified the three most influential factors affecting model outcomes: discount rate, costs associated with progressive disease, and utility value for progression-free survival. Probabilistic sensitivity analysis indicated that at a WTP threshold of $37,709.46 per QALY, the probability of penpulimab being cost-effective reached 99%. Scenario analyses demonstrated that, while the base-case results were generally robust, the cost-effectiveness of penpulimab remained sensitive to the limited maturity of overall survival (OS) data in the penpulimab group. The immaturity of the OS data increased the extrapolation uncertainty, which could potentially alter the economic conclusions.ConclusionPenpulimab, in combination with paclitaxel and carboplatin, demonstrates a cost-effectiveness advantage over placebo as a first-line treatment for advanced or metastatic squamous NSCLC in China, provided that long-term survival benefits align with extrapolations from the base case model. These findings support its prioritization in clinical practice within the current WTP thresholds. However, the economic conclusions remain contingent on resolving the uncertainties associated with immature OS data and validating extrapolation assumptions through extended follow-up studies.